Growth promotion of crop plants by Methylobacterium organophilum: Efficient bio-inoculant and bio-fertilizer isolated from mud - Rekadwad, Bhagwan Narayan (Research in Biotechnology, 2014)
Nitrogen fixing bacterium was isolated from mud near hot springs located at Unkeshwar in Nanded district, Maharashtra, India. Gram negative, oval rod, motile bacterium using nutrient broth medium from mud samples. Isolate bacterium showed luxuriant growth at 45oC temperature and pH 8. Isolate also showed growth on Azatobacter-Mannitol agar. The isolated species identified as Methylobacterium organophilum using morphological and biochemical tests. Isolate capable of growth at 5% salt concentration and alkaline pH. Isolate was used as growth promoting agent. Effect of isolate on germination of seeds; their ability of plant growth promotion was also studied. Remarkable growth of Vigna radiate was observed in the presence of isolated thermophilic Methylobacterium sp.